2015
DOI: 10.1007/s12544-014-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

A new urban freight distribution scheme and an optimization methodology for reducing its overall cost

Abstract: Purpose The paper refers to an innovative urban freight distribution scheme, aimed at reducing the externalities connected with the freight delivery process. Both packages destined to commercial activities and to end consumers (e-commerce) are taken into account. Each package is characterized by an address and dimensions. In the proposed transport system, freight is firstly delivered to the UDC on the border of urban areas through trucks or trains which perform the long distance transport. After, freight is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…As shown in Rose et al (2017), urban areas are characterized by the interplay of different stakeholder interest in close quarters, and, as highlighted in Kin et al (2017), megacities add growing sustainability challenges. Further obstacles include low load factors, empty trips, long dwell times at loading and unloading points, and large numbers of deliveries to individual customers (Cepolina and Farina, 2015). The key challenge for the future is rethinking the way existing infrastructure is used and how new infrastructure is built, so that it is fully utilized and negative externalities are minimized.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Rose et al (2017), urban areas are characterized by the interplay of different stakeholder interest in close quarters, and, as highlighted in Kin et al (2017), megacities add growing sustainability challenges. Further obstacles include low load factors, empty trips, long dwell times at loading and unloading points, and large numbers of deliveries to individual customers (Cepolina and Farina, 2015). The key challenge for the future is rethinking the way existing infrastructure is used and how new infrastructure is built, so that it is fully utilized and negative externalities are minimized.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There are many studies on the impact of vertical collaboration on urban logistics practice that do not necessarily address OR models. Cepolina and Farina (2015) consider the transport of standardized load units ("FURBOT boxes") and discuss alternatives such as pack stations and bento boxes. The FURBOT system supports the consolidation of packages with multiple destinations into a single unit with multiple, lockable doors, ensuring the security of the freight en route to its destination.…”
Section: Urban Consolidation Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have demonstrated that the cutting plane algorithm for scheduling therapy jobs and routing therapists hospital-wide can substantially reduce solution times. We argue that the approaches can be generalized for solving other problem instances in other service industries such as parcel delivery in which delivery locations are flexible (Cepolina and Farina (2015)).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Cluster analysis can help in this case, since it is a technique aiming at finding collections of objects such that the elements in a group will be similar (or related) to one another and different from (or unrelated to) the elements in other groups [25]. Examples of exploitation of this data mining methodology can be found in different domains of transport engineering such as transit quality evaluation [26] or tours classification [27], while its use in urban logistics can be exploited for the organization of deliveries according to city's characteristics [28] or the optimization of freight transport system's performances [29].…”
Section: Selection Of a Subset Of Stops Through Spatial Clusteringmentioning
confidence: 99%